(untitled) (The Journal of Theoretical Accounting Research, 2025)
As the world has turned into a competitive environment, organization with technological change and complexity, Strategic Human Resource Management (SHRM) combination with functional functions such as accounting, finance, business administration and organizational behavior has become a critical component of guaranteeing a sustainable competitive advantage. The paper provides a comprehensive integrative model that correlates SHRM activities with financial responsibility, behavioral efficiency, and strategic responsiveness. The study relies on the Resource-Based View (RBV) and the Ability-Motivation-Opportunity (AMO) theory in the conceptualization of human capital as a dynamic strategic resource that enables actual financial performance and intangible behavioral prospects. The study will be based on a mixed-method format and will imply the incorporation of quantitative and qualitative information gathered by the corporate HR and finance departments and semi-structured interviews with senior managers, respectively. The analysis looks at the mediating variable of organizational behavior particularly motivation, engagement and culture and the moderating variable of accounting transparency and financial governance. Findings show that, the strategic alignments within the HR practices enhance the culture of high performance, cross-functional cooperation and financial performance under the condition of good financial management and business strategy. The theoretical contribution of the study is the integration of functional silos through interdisciplinary model of SHRM and gives practical implications to the executives who want to balance human capital policies with corporate and financial objectives. The integrative approach helps in the formulation of the argument regarding strategic management since SHRM is at the heart of sustainable performance of organizations.